Theoretical Spectroscopic Study for Some Diatomic Molecules - Ayyash, Adil Neama (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, four electronic states ( , , and ) of some diatomic molecules (InF and InCl) was studied by TD-DFT with energy represented by the exchange-correlation energy. The SAOP/ATZP model was applied here to determine all parameters (re, Be, De, , , Te , and were determined to creation reliable values for electron spectroscopy. Also, another set of this calculation has been used represented by two theoretical models: ATZP and et-QZ3P-xD model. Therefore these theoretical models for ( and , and ) of the molecules have been compared with many values, theoretical and experimental values, and appear convergence in values with simple error %. Our results showed that the TD-DFT with basis set in the present work is important for the estimation of spectroscopic parameters and constants for our molecules and the ATZP model is very close to et-QZ3P-xD model in all electronic states for InF and InCl molecules except some of the constants such as (Be).